Pengaruh Kompetensi dan Komunikasi Pelaksanaan Work From Home terhadap Kinerja Aparatur Sipil Negara di Lingkungan Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Utara di Masa Pandemi Covid-19 - Sutanti, Hesti; Matodang, Sofiyan; Marpaung, Fenny Krisna (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to determine the effect of competence on the performance of the State Civil Apparatus (ASN) during Work From Home (WFH) during the pandemic and the effect of communication on the performance of ASN during WFH during the pandemic and to analyze the factors inhibiting performance (ASN) in the Council Environment. Regional People's Representatives (DPRD) of North Sumatra Province (Provsu). This research uses ASN Competency Theory, ASN Performance and Communication. This research was conducted at the Provincial DPRD Office. The research method used in this research is correlational quantitative. The population in this study were civil servants at the provincial government DPRD office which accommodated 106 people. Sampling in this study using total sampling. The results of this study include: (1) There is an effect of ASN Competence on ASN Performance in the Provincial DPRD Environment during the pandemic period of 0.707. the second variable is positive and strong (2) There is an influence of ASN Communication on the performance of ASN in the DPRD Pemprovsu environment of 0.383. The level of correlation is low but definite between ASN communication variables and ASN performance during WFH in the DPRD Pemprovsu environment; (3) Factors that hinder performance are abilities that are motivated by differences in generations which are dominated by the Baby Boomer Generation over 45 years old, lack of motivation, ability to use technology, so that it has obstacles in production development.